Determinants of services quality towards Islamic banking performance in Malaysia / Amirah Shahirah Mahmood - Mahmood, Amirah Shahirah (Faculty of Business and Management, 2015)
Islamic banking is an emerging global industry which based on Islamic ethical. Malaysia is indeed a leader of Islamic banking, started with Bank Islam Malaysia Berhad (BIMB) on 1983. Islamic banking in Malaysia exists due to help Muslims to invest and save their money in a right way without any corruption. Islamic banking also needs to survive by competing with other conventional banking systems. Hence, this study is to investigate customers’ satisfaction towards the service quality provided Islamic banking performance in Malaysia. Customer satisfaction is the degree of satisfaction from some people who are using the product or services provided by one institution. In facing a new technology environment, bank should provide instruments that could satisfy current and future customers to use their product and services as it is the key to success on development and expansion of banks. The aim on this study is to identify the most factors that effect on the customer satisfaction and the relationship of tangibility, reliability, responsiveness, assurance, empathy and convenience towards customer satisfaction in Islamic banking.